Theoretical requirements and inverse design for broadband perfect absorption of low-frequency waterborne sound by ultrathin metasurface - Jie Zhong (Nature Portfolio, 2019)
Abstract Effective absorption of low-frequency waterborne sound with subwavelength absorbers has always been a challenging work. In this paper, we derive two theoretical requirements for broadband perfect absorption of low-frequency waterborne sound by ultrathin acoustic metasurface under a finite-thickness steel plate followed by semi-infinite air. Based on the theoretical requirements, an acoustic metasurface, a rubber layer embedded periodically with cavities, is inversely designed to achieve perfect absorption at 500 Hz. The metasurface is as thin as 1% of the working wavelength and maintains a substantially high absorptance over a relatively broad bandwidth. The perfect absorption peak is attributed to the overall resonance mode of the metasurface/steel plate system. Besides, high absorption can still be achieved even if the loss factor of the given rubber material cannot meet the ideal requirement. Finally, a strategy to utilize the inherent frequency-dependent characteristics of dynamic parameters of rubber material is suggested to achieve an ultra-broadband perfect absorption. When the frequency-dependent characteristics of the given rubber matrix cannot meet the theoretical requirements, a broadband super-absorption can still be realized by properly designing the frequency position of perfect absorption of the cavity-based metasurface.